A Review of “The Qur’an: What Everyone Needs To Know” by Jane McAuliffe - Bayram Kara (Darulfunun Ilahiyat)
Jane McAuliffe. The Qur’an: What Everyone Needs To Know (New York: Oxford University Press, 2020), 218 Syf. ISBN: 978-0-19-086768-3